Oral history interview with Patricia "Pat" Wetherington Brockinton, September 4, 2003 - Brockinton, Patricia Wetherington (Valdosta State University Archives and Special Collections, 2003)
Oral history interview with Patricia "Pat" Wetherington Brockinton, September 4, 2003. Fargo (Ga.), Dayton Turpentine Camp site. Fieldworker: Laurie Sommers. Audio file digitized from cassette tape. Part of the South Georgia Folklife Project at Valdosta State University Archives and Special Collections. Topics include Turpentine and Turpentine industry and trade.
1 electronic record(s) and derivatives. 1 audio file (wav, mp3) 557,380,808 bytes. 01:45:19. 4 PDF documents (19 scans, jp2). 1.50 GB (1,612,556,785 bytes).
Keywords: Georgia; Oral history; Sound recordings; Brockinton, Patricia Wetherington (1935-2012); Turpentine; Turpentine industry and trade; Naval stores; Fargo (Ga.)